Impact of milking frequency on yield, chemical composition and quality of milk in high producing dairy herd - Paweł Bortacki; Ryszard Kujawiak; Ewa Czerniawska-Piątkowska; Seval Sevgi Kirdar; Jerzy Wójcik; Wilhelm Grzesiak (Mljekarstvo)
The aim of this study was to compare daily yield, milk composition and somatic cell count after increasing milking frequency from twice to three times a day. The study also includes the effect of other factors such as: the sequence of lactation (1, 2, ≥3) and the period of lactation (100 days, 101-200 days, 201-300 days, and more than 300 days). In conclusion, it should be noted that increasing the frequency of cow milking had a positive effect both on the milk yield (P≤0.01), causing a substantial increase, as well as on the cytological quality of produced milk. The somatic cell count (1000/mL) was lower in the group of cows milked three times a day. All the data regarding farming records of this farm came from the SYMLEK system maintained and made available by Polish Federation of Milk Producers and Cattle Breeders (PFHBiPM). Analysis of useful milk traits included: daily yield, fat, protein, dry matter and somatic cell count in milk.